Legal Analysis of Trademark Patent Dispute i AM Geprek Bensu Against Geprek Bensu - Kevin Halomoan; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Patents guarantee the presence of a mark of ownership. This patent is granted to patent holders who are entitled on the basis of ownership of a name, item or product. This patent holder gets treatment for his right to prevent other parties from imitating, simulating, and making a similar product name for a certain period of time. In essence, this patent is granted on the basis of the inventor of an idea who is motivated by his innovation in making and bringing out a new invention that can be applied industrially based on research results from experience. The acceptance of this patent gives rise to a special treatment because of the honor of having made a new invention which will later be considered as a property that cannot be used, shared, and imitated by others.